Ureteric Injuries During Gynecological Procedures and Repair - Muhammad Asif, Muhammad Sohail, Shumaila Yasin, Muhammad Shakeel Anjum, Zakariya Rashid, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Injury to the ureter is a risk of any pelvic or abdominal surgery. The anatomic proximity of the lower urinary tract and the female reproductive system renders the ureter vulnerable to injury during obstetric and Gynecologic procedures. Ureterovaginal fistula is an uncommon but serious sequela of unrecognized distal ureteral injury during pelvic surgeries because of their common embryologic origin. Method: This study involved a series of 25 patients, who developed ureterovaginal fistula after Obstetric and Gynecologic procedures managed in urology department Muhammad Islam teaching hospital Gujranwala. These patients were managed with open Ureteroneocystostomy, within 2 weeks of primary procedure. In this study we present our postoperative result of 6 months of follow up. Results: All patients were cured (100%) with complete cessation of urinary fistula with complete restoration of renal function and complete restoration of urinary anatomy. Conclusion: The results of our study showed that the patient with Ureteric injury should be evaluated and intervened at the earliest. Early identification and repair of ureterovaginal fistulas results in a high quality of life, less postoperative complications, and a high success rate and preservation of renal function. keywords: Ureteric injury, ureterovaginal fistula.